Regulation of the RNA‐binding protein Smaug by the GPCR Smoothened via the kinase Fused. (8th May 2020) - Bruzzone, Lucia; Argüelles, Camilla; Sanial, Matthieu; Miled, Samia; Alvisi, Giorgia; Gonçalves‐Antunes, Marina; Qasrawi, Fairouz; Holmgren, Robert A; Smibert, Craig A; Lipshitz, Howard D; Boccaccio, Graciela L; Plessis, Anne; et al.
Abstract: From fly to mammals, the Smaug/Samd4 family of prion‐like RNA‐binding proteins control gene expression by destabilizing and/or repressing the translation of numerous target transcripts. However, the regulation of its activity remains poorly understood. We show that Smaug's protein levels and mRNA repressive activity are downregulated by Hedgehog signaling in tissue culture cells. These effects rely on the interaction of Smaug with the G‐protein coupled receptor Smoothened, which promotes the phosphorylation of Smaug by recruiting the kinase Fused. The activation of Fused and its binding to Smaug are sufficient to suppress its ability to form cytosolic bodies and to antagonize its negative effects on endogenous targets. Importantly, we demonstrate in vivo that HH reduces the levels of smaug mRNA and increases the level of several mRNAs downregulated by Smaug. Finally, we show that Smaug acts as a positive regulator of Hedgehog signaling during wing morphogenesis. These data constitute the first evidence for a post‐translational regulation of Smaug and reveal that the fate of several mRNAs bound to Smaug is modulated by a major signaling pathway. Synopsis: The RNA interacting protein Smaug binds Smoothened and in response to Hedgehog signaling is phosphorylated reducing its mRNA repressive activity. Smoothened, a G‐protein coupled receptor family member, interacts with the RNA‐ binding protein Smaug and promotes its phosphorylation by the kinase Fused. Phosphorylation of Smaug reduces its levels, mRNA repressive activity and ability to form cytoplasmic foci. Smaug acts as a positive modulator of Hedgehog signaling. Abstract : The RNA interacting protein Smaug binds Smoothened and in response to Hedgehog signaling is phosphorylated reducing its mRNA repressive activity.